2013
DOI: 10.1021/jz401850h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient N2 Formation on Ag(111) by Eley–Rideal Recombination of Hyperthermal Atoms

Abstract: Using molecular dynamics simulations and potential energy surfaces of ab-initio quality, we show that direct pick-up of N adsorbates by gas-phase N is a highly efficient channel for N 2 formation on Ag(111). This recombination process, called Eley-Rideal, was traditionally associated to lighter projectiles and regarded as marginal, but here we obtain reactivities for * To whom correspondence should be addressed TOC GraphicKeywords: Gas-surface interactions, Eley-Rideal reactions, scattering, potential energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…It is at this stage when nowadays simulations based, mostly, on density functional theory (DFT) are the necessary counterpart to fully understand the properties governing these processes and to confirm the interpretation of the experimental outcome. 4,[11][12][13] In this respect, there are various examples showing that not only the reactivity [14][15][16] but also scattering properties such as the diffraction peaks positions, 17,18 angular distributions, [19][20][21][22][23] rotational states, [24][25][26][27][28] and energy loss 21,23,29 are reasonably described by this level of theory. Considering that in all these cases, the potential energy surfaces (PESs) have been calculated with the (hitherto standard) semilocal exchange-correlation (xc) functionals that do not correctly describe the long-range van der Waals (vdW) interaction, such an agreement is somehow unexpected at first thoughts.…”
Section: Introductionmentioning
confidence: 91%
“…It is at this stage when nowadays simulations based, mostly, on density functional theory (DFT) are the necessary counterpart to fully understand the properties governing these processes and to confirm the interpretation of the experimental outcome. 4,[11][12][13] In this respect, there are various examples showing that not only the reactivity [14][15][16] but also scattering properties such as the diffraction peaks positions, 17,18 angular distributions, [19][20][21][22][23] rotational states, [24][25][26][27][28] and energy loss 21,23,29 are reasonably described by this level of theory. Considering that in all these cases, the potential energy surfaces (PESs) have been calculated with the (hitherto standard) semilocal exchange-correlation (xc) functionals that do not correctly describe the long-range van der Waals (vdW) interaction, such an agreement is somehow unexpected at first thoughts.…”
Section: Introductionmentioning
confidence: 91%
“…One of the closest examples to date is the indication of N abstraction of N from Ag(111) [20]. While the presence of a large N 2 component in the incident beam precludes definitive assignment on the sole basis of the measurements, molecular dynamics (MD) simulations validate the inference of an ER reaction [21]. A similar issue affects attribution of a possible ER process in the case of hyperthermal O interaction with graphite [22].…”
mentioning
confidence: 99%
“…The latter indicates an energydependent reaction probability, leading to suppression of direct reaction in the case of the highest energy N atoms. MD simulations of N abstraction of N from Ag(111) have found a significant energy dependence, with the reaction probability decreasing at higher incident energies [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the abstraction of adsorbed O and N atoms on Ru(0001) was shown with an effusive beam of neutral nitrogen species (N þ N 2 ) [16]. In computational studies of N-atom abstraction by energetic N on Ag(111), ER reactions were shown to be highly efficient [17]. Most of these studies focused on proving that the molecular product is indeed produced by an ER reaction.…”
Section: Direct or Eley-rideal Reactions Between Energetic Nmentioning
confidence: 99%